TOPSIS prefabricated building construction evaluation based on interval-valued Pythagorean fuzzy numbers based on prospect theory - Lixin Chang; Norhaiza Nordin; Shiwei Zhao; Xinhua Gu; Ye Zhao (Scientific Reports)
Abstract Prefabricated buildings have a series of advantages such as high efficiency, energy savings, and environmental protection, and are being strongly promoted by the Chinese government. However, due to the late start of prefabricated buildings in China, the installation process of prefabricated components is relatively complex, leading to difficulties in quality and safety control. A novel evaluation methodology integrating the technique for order preference by similarity to ideal solution (TOPSIS) with prospect theory and interval-valued Pythagorean fuzzy numbers (IVPFNs) is proposed. Fully considering the subjective value perceptions of decision-makers when faced with losses and gains, a risk evaluation model is established based on different types of decision-makers. This model is then compared with the weight correction coefficient model from a balanced perspective to prevent bias caused by over-reliance on decision-makers’ subjective preferences. This study establishes an assessment index system for assembly construction risk, considering personnel, materials, machinery, management, and technology factors. By merging prospect theory with the TOPSIS method, the application of Pythagorean fuzzy numbers is refined, enhancing the group decision-making process for evaluating risks in prefabricated construction projects. On the other hand, the prospect theory approach can focus on the actual psychological state of managers during decision-making, addressing the research gap concerning the impact of managers’ psychological states on the evaluation process. The study identifies critical risk factors and suggests specific risk management strategies to improve the risk mitigation capabilities of construction entities, offering a structured approach to enhancing the efficiency and safety of prefabricated construction projects.